Silver Hues : Building Age-Ready Cities - Das, Maitreyi Bordia; Yuko, Arai; Chapman, Terri B.; Jain, Vibhu (World Bank, Washington, DC, 2022)
Cities and countries the world over are at the cusp of epochal global trends whose impacts are likely to be more intense and more far-reaching than those of similar trends in the past. The simultaneity of the demographic transition, deepening urbanization, a technological revolution, frequent shocks brought on by health and climate emergencies, mean that one will need to plan for an older and more urban future. This report is intended as a policy document that helps articulate the idea of age-readiness while building on the idea of age-friendliness. It highlights the varied trajectories of aging and urbanization and draws on the experiences of older and more urban countries to show how others can become age-ready. It is intended for cities and towns as they prepare for an older urban age, offering examples and options to help younger cities visualize age-readiness while focusing primarily on the built urban environment. Its main audience is intended to be policymakers, city leaders, and implementing agencies, but it is also expected be useful to researchers, nongovernmental organizations, the private sector, and communities.